2017
DOI: 10.21042/amns.2017.1.00009
|View full text |Cite
|
Sign up to set email alerts
|

Affine Transformation Based Ontology Sparse Vector Learning Algorithm

Abstract: In information science and other engineering applications, ontology plays an irreplaceable role to find the intrinsic semantic link between concepts and to determine the similarity score returned to the user. Ontology mapping aims to excavate the intrinsic semantic relationship between concepts from different ontologies, and the essence of these applications is similarity computation. In this article, we propose the new ontology sparse vector approximation algorithms based on the affine transformation tricks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In order to accurately recognize face images, it is necessary to perform posture correction and noise reduction on the face images. Using wavelet denoising method, the geometric structure models of face images with different attitude features are first given [1]. Feature extraction and sample collection are performed on face models in different poses, and an affine transformation between two vector spaces with face image features is constructed in rotation coordinates [2,3].…”
Section: Noise Reduction Of Face Imagesmentioning
confidence: 99%
“…In order to accurately recognize face images, it is necessary to perform posture correction and noise reduction on the face images. Using wavelet denoising method, the geometric structure models of face images with different attitude features are first given [1]. Feature extraction and sample collection are performed on face models in different poses, and an affine transformation between two vector spaces with face image features is constructed in rotation coordinates [2,3].…”
Section: Noise Reduction Of Face Imagesmentioning
confidence: 99%
“…The core of raindrop removal for single image based on deep learning is to design a more effective end-to-end mapping model of raindrop image and rainless image to achieve the repair of raindrop area [13]. VDSR (very deep networks for Super-Resolution) is a kind of feedforward deep convolution neural network based on deep learning.…”
Section: Raindrop Removal Model Based On Deep Learningmentioning
confidence: 99%
“…Experiment shows that the change of temperature and heat transfer conditions at the cold end has little effect on the output performance [11]. At the same time, researchers found that contact pressure, cold source structure and cooling mode also affect the output performance of thermoelectric generator [12][13][14].…”
Section: Introductionmentioning
confidence: 99%